Vicarious Calibration Site Selection For Razaksat™ Medium-Sized Aperture Camera (Mac) - Lee, Yee Hwai; Hashim, Mazlan; Arshad, Ahmad Sabirin (2007)
RazakSAT™ Medium-sized Aperture Camera (MAC) will be Malaysia’s first calibrated earth observation satellite. Vicarious calibration is crucial to ensure the data quality of RazakSAT™ MAC since it carries no onboard calibrator. RazakSAT™ MAC’s low inclination (9o) orbit is in the near-equatorial region and thus, commonly used vicarious calibration sites such as deserts, dry lakebeds, playas, etc are not accessible. The main objective of this study is to determine the optimum sites, consisting of either natural and/or artificial targets, for the vicarious calibration of RazakSAT™ MAC. The criteria for the selection are based on a list of desired characteristics for a reflectance-based vicarious calibration approach from previous works by other researchers. RazakSAT™ MAC has a spatial resolution of 2.5m and 5.0m for panchromatic and multispectral band respectively. Studies found that chosen sites have to be larger than 15mx15m in size, which is equivalent to the 3x3 pixels requirement of RazakSAT™ MAC’s spatial resolution. The suitability of determined targets and sites were assessed based on their reflectance and homogeneity using a field spectroradiometer. The optimal natural targets determined from this study’s analyses are fine sand and small rocks, and optimal artificial target is tarpaulin. The sand and rocks have reflectance values greater than 0.4 while the tarpaulin’s reflectance is greater than 0.7, adequate for calibration of all RazakSAT™ MAC bands. Furthermore, all these three targets are very homogeneous with almost constant spectral curves.